Perencanaan Layout 3D untuk Sistem Pengolahan Air Limbah di Kapal Penumpang - Pramesti, Lely (Politeknik Negeri Jakarta, 2025)
As an archipelagic nation, Indonesia relies heavily on passenger ships to maintain inter-island connectivity. However, the operation of these vessels generates domestic wastewater that may cause marine pollution if not properly managed. A vacuum based piping system offers an efficient technical solution especially suitable for limited onboard space. This study aims to design a 3D layout of a vacuum assisted sanitary wastewater collection system and to calculate the required vacuumarator capacity to transfer waste from toilets and sinks to a holding tank for further treatment by STP. The research applied an engineering design approach consisting of five stages: regulatory review, technical data collection, vacuum capacity calculation, component specification comparison, and 3D modeling. Results show that the required vacuum capacity ranges from 490 to 840 flushes per hour, depending on whether ISO or vendor calculation. The Jets 15MB-D was selected due to its compatibility with the minimum STP capacity, energy efficiency, lightweight and compact, and suitability with DN40 pipe connections. The 3D layout places the vacuumarator near the STP to minimize pressure loss and simplify maintenance. The proposed design complies with MARPOL Annex IV and BKI rules and can serve as a reference for retrofitting sanitary systems on domestic passenger ships.